Screening performance of congenital heart defects in first trimester using simple cardiac scan, nuchal translucency, abnormal ductus venosus blood flow and tricuspid regurgitation. (1st October 2019) - Karadzov Orlic, Natasa; Egic, Amira; Damnjanovic‐Pazin, Barbara; Lukic, Relja; Joksic, Ivana; Mikovic, Zeljko
Abstract: Objective: The objective of this study was to analyze if the addition of simple cardiac scan in cases with increased nuchal translucency (NT) and/or abnormal ductus venosus (DV) blood flow, and/or tricuspid regurgitation (TCR) can improve detection of congenital heart defects (CHD) in chromosomally normal fetuses without non‐cardiac defects at 11‐13 + 6 gestational weeks in a population of singleton pregnancies. Methods: During the 10 years period, all singleton pregnancies at 11‐13 + 6 weeks were routinely scanned for NT, DV blood flow and TCR assessment and, if a single of these parameters was abnormal, simple cardiac scan with 2D gray scale and color and/or directional power Doppler in 4‐chamber (4‐CV) and 3 vessel and trachea views (3VTV) was performed. Results: The sensitivity and specificity of NT ≥ 95th + DV R/A a‐wave + TCR in detecting CHD were 77% and 97%, respectively, and of simple cardiac scan, 67% and 98%, respectively. Area under the curve of receiver operating characteristic curve of NT ≥ 95th + DV R/A a‐wave + TCR was 0.838, and of NT ≥ 95th + DV R/A a‐wave + TCR + simple cardiac scan was 0.915. Conclusions: In chromosomally normal fetuses without non‐cardiac anomalies, addition of simple cardiac scan to the combined first trimester screening parameters improves detection of major CHD during first trimester.